The Ethics of Prioritizing Access to Palliative Care: A Qualitative Study. (July 2019) - Philip, Jennifer; Russell, Bethany; Collins, Anna; Brand, Caroline; Le, Brian; Hudson, Peter; Sundararajan, Vijaya
Palliative care services are increasingly required to consider issues of resource, management as demand for services increases. The processes of triage have been developed in health care as a means of balancing need and resources in an equitable and reproducible way. Objective: This article sought to explore ethical issues associated with prioritization decisions in palliative care. Methods: As part of a broader series of studies of triage in palliative care, this qualitative substudy was conducted via semi-structured focus groups and individual interviews. Transcripts were subjected to thematic analysis. Setting/Participants: Twenty health professionals working across disciplines (primary, specialist; medicine, nursing, and allied health), service types (inpatient, hospital liaison, and community), and locations (metropolitan and rural) in Victoria, Australia. Results: Four themes emerged from the data: (1) Clinicians understood the tension between maintaining service quality with the delivery of a compromised service that sought to respond to demand. (2) They were aware of the influences of relationships and responsibilities upon patient waiting list prioritization, and (3) reported a hierarchy of suffering with certain types of clinical problems viewed as more urgent than others, for example, pain being more urgent than existential distress. (4) Clinicians noted a lack of transparency around waiting lists as they currently exist. Conclusions: This study revealed key ethical decision-making issues associated with prioritizing access to palliative care services. Making explicit the processes and influences upon decision-making provides greater transparency of health-care utilization at the end of life.